2022
DOI: 10.1007/s12672-022-00556-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of Nrf2 signaling in glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is one of the most aggressive glial cell tumors in adults. Although current treatment options for GBM offer some therapeutic benefit, median survival remains poor and does not generally exceed 14 months. Several genes, such as isocitrate dehydrogenase (IDH) enzyme and O6-methylguanine-DNA methyltransferase (MGMT), have been implicated in pathogenesis of the disease. Treatment is often adapted based on the presence of IDH mutations and MGMT promoter methylation status. Recent GBM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…The transcription factors Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2), Nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB), and tumor protein p53 (p53) control inflammatory and stress responses, thereby supporting GBM survival; they are also linked to the UPR (Figure S13A). Nrf2 protects against oxidative stress, promotes anti-apoptotic and anti-inflammatory responses, and stimulates cell proliferation . High-grade GBM cells often contain elevated levels of Nrf2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcription factors Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2), Nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB), and tumor protein p53 (p53) control inflammatory and stress responses, thereby supporting GBM survival; they are also linked to the UPR (Figure S13A). Nrf2 protects against oxidative stress, promotes anti-apoptotic and anti-inflammatory responses, and stimulates cell proliferation . High-grade GBM cells often contain elevated levels of Nrf2.…”
Section: Resultsmentioning
confidence: 99%
“…Nrf2 protects against oxidative stress, promotes anti-apoptotic and anti-inflammatory responses, and stimulates cell proliferation. 59 High-grade GBM cells often contain elevated levels of Nrf2. This improves GBM survival and is linked to poorer treatment outcomes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that there is no difference in the mechanism in which NRF2 promotes cell protection, and that the only difference is in the scenario in which the cell is protected: for normal cells, NRF2 activation occurs in a controlled and transient manner, whereas for tumor cells, NRF2 is constitutively activated, conferring cytoprotection and leading to chemotherapy resistance [ 42 ]. Therefore, since NRF2 is a key molecular player involved in many fundamental cellular responses to chemotherapy, it has been explored over the past years as a promising therapeutic pathway in glioblastoma [ 43 ]. In this sense, a recent study from our group, utilizing CRISPR library screening, identified NRF2 as one of the main targets in the context of TMZ resistance, further emphasizing the importance of this pathway in glioblastoma [ 44 ].…”
Section: Nrf2mentioning
confidence: 99%
“…Intriguingly, KEAP1-USP11 defective tumor cells exhibit BRCAness phenotype, i.e., alteration of R-loops homeostasis, DNA damage, and higher sensitivity to PARP inhibitors [ 116 , 117 ]. Therefore, SETX might represent a therapeutically actionable target to modulate the cytotoxic response of those tumor types carrying aberrant USP11-KEAP1-NRF2 pathway [ 118 120 ]. Therefore, a deeper comprehension of the circuits controlling SETX expression might be relevant to unveil novel therapeutically actionable routes in neurological disorders as well as human cancers.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%